This country : [large type] my life in politics and history - Matthews, Chris, 1945- (Wheeler Publishing, a part of Cengage Company, 2021)
The former host of MSNBC's "Hardball with Chris Matthews" offers a panoramic portrait of post-World War II American politics through the story of his extraordinary life and career